Avaliação pedagógica para definição de atendimento em sala de recursos de deficiência intelectual na percepção de professores especialistas - Heradão, Julia Gomes (Universidade Federal de São Carlos, 2014)
Brazilian reality in the proposed construction of an educational system that embraces all children is supported by legally and theoretical bases that underlie their ideas on principles of equality, fairness and diversity. However, often, the school educational practices moving away from theoretical propositions. Contact with the school reality, especially with the teachers of resource rooms, makes it possible to perceive the problem involving the realization of an educational evaluation to decision frequency of these students in resource rooms Intellectual Disabilities. Faced with this situation was elaborated question: What aspects are relevant in the process of developing a pedagogical review for defining services in the resources of Intellectual Disabilities room? What conditions are favoring and not favorable this process? To attempt to answer these research questions were proposed as objectives: 1) Identify and analyze the instruments and procedures suggested by the teachers of resource rooms intellectual disabilities in developing a pedagogical review. 2) Check which aspects contributed and which hampered the development of a pedagogical evaluation by teachers of resource rooms intellectual disability. To investigate this study was based on a qualitative approach with characteristics of participatory research. Participants were five teachers of resource rooms intellectual deficiency state schools in a city in the state of São Paulo . The teachers participated in meetings organized in the form of a focus group. These encounters were filmed and had discussions as a generator of Annex I of the ESS Resolution 11 /2008. Following each meeting the information observed were recorded in a diary, as a complementary tool for data collection. The information obtained through the filming received the following treatment: a) verbatim filming b) identification of issues discussed at each meeting; c) formulation of themes relating to the types of issues discussed by the group, d) a description of the results from the information relating to each theme category in terms of aspects of the planning and evaluation process addressed by the participants; alternative presented by participants regarding the issues discussed , pros , cons , criteria or justifications; aspects mentioned and not discussed, results discussion and referrals; considerations of the researcher. Data were analyzed in view of the thematic categories for types of issues discussed by the group, the notes recorded in the field diary, objectives and theoretical framework. As a result indicated by the teachers including the following instruments for the realization of educational evaluation: Data routing students to educational evaluation; Script interview with the student; Sheet structured interviews with parents and Activities to be performed by students. In general, the participants seem to have built an educational evaluation, enabling them to find characteristics indicating the student is the target audience of intellectual disability resource room.
Keywords: Educação especial; Deficiência mental; Deficiência intelectual; Avaliação pedagógica; Sala de recursos; Intellectual disability; Special education; Educational assessment; Resource room; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL